Enhancement of Charge Transfer in TiO2/BiOI Heterojunction Using BiFeO3 as Interface Modifier for Photoelectrochemical Conversion. Issue 11 (26th November 2021) - Jiang, Yuanyuan; Pathak, Rajesh; Zhang, Tiansheng; Xu, Haibin; Li, Xiaoyi; Jian, Ronghua; Wu, Fan
Abstract : The solution-processed TiO2 /BiFeO3 /BiOI ternary heterojunction with cascade energy level alignments was developed for photoelectrochemical conversion, in which, BiOI was deposited on BiFeO3 sensitized TiO2 mesoporous film by spin-coating method. BiFeO3 as ferroelectric material was served here as a mediator for improvement of charge separation and transfer. The photocurrent generation in TiO2 /BiFeO3 /BiOI sample are very stable, even measured after 50 light on/off cycles with 2000 s. Moreover, compared with the TiO2 /BiOI film, TiO2 /BiFeO3 /BiOI film showed about twice as high photocurrent density and photocatalytic activity. Kelvin probe force microscope showed that the surface potential of TiO2 /BiFeO3 /BiOI film was 0.456 V, which was obviously larger than 0.226 V in TiO2 /BiOI sample. The increased surface potential should originate from the polarization electric-field E self by BiFeO3 interlayer, in which the direction of electric-field was directed toward the BiOI. The presence of E self consequently resulted in the better dissociation of photo-generated electrons and holes. Charge transport dynamics suggested that charge transfer rate increased from 6.813 s −1 of TiO2 /BiOI heterojunction to 22.280 s −1 of TiO2 /BiFeO3 /BiOI heterojunction, and surface charge recombination rate reduced from 10.305 s −1 of the TiO2 /BiOI to 7.707 s −1 of TiO2 /BiFeO3 /BiOI heterojunction, which results in the enhanced photoelectrochemical conversion in TiO2 /BiFeO3 /BiOI heterojunction.